Angled cavity photonic crystal lasers with asymmetrical high-order surface gratings. (10th February 2017) - Liu, Yun; Wang, Yufei; Qu, Hongwei; Zhao, Shaoyu; Li, Lunhua; Zheng, Wanhua
Abstract: 980 nm angled cavity photonic crystal (PC) laser diodes with asymmetrical high-order surface gratings (aHSGs) are proposed and fabricated. The one-dimensional PC structure in the epitaxy is used to expand the fundamental transverse mode and reduce the vertical divergence. An angled cavity with aHSGs is fabricated to achieve a nearly diffraction-limited beam quality and narrow spectral width. Experimentally, a continuous-wave output of 0.85 W/facet, a low divergence of 1.5 × 10.6°, and a narrow spectral width of 0.07 nm are achieved. The lateral beam quality is superior with an of 1.96.